(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Currently, in developed countries, where information technology has taken a leading role, it has become necessary to update the system of schools, the content of education. The methods and techniques of teaching the old are spiritually outdated, and the need for methods and forms of education based on advanced pedagogical technologies has increased.